HEALTH STATUS AND SOME GENES POLYMORPHISM IN CHILDREN OF NORTHERN AREAS OF THE ZABAYKALSKY KRAI - G. I. Bisharova; N. I. Zubina; E. E. Gergesova; O. E. Bartuhina; T. A. Chuprova (Acta Biomedica Scientifica, 2013)
The aim of the present work was the study of children's health in the Northern areas of the Zabaykalsky Krai. The study was conducted on the territory of Tungokochenskiy, Tungiro-Olekmenskiy and Kalarskiy areas. A random sample of 1339 children and adolescents of indigenous population and newcomers to the Northern regions was examined, including 254 Evenks. Conducted examinations of employees of Regional Children Consultation and Diagnostic Center; functional diagnostics, ultrasound diagnostics; laboratory diagnostics: determination of urinary iodine ионоселективным method, ELISA screening helminthes, evaluation of the humoral immunity, evaluation of hormonal status, study GSTP1 polymorphism of genes (Ile105Val), TNF-alpha (G308A), IL-10 (G1082A) and IL-4 (C589T) using PCR-Rv children of indigenous peoples of the Northern regions of the Zabaykalsky Krai (Evenk). On the basis of the analysis of the results of field work the following results were received: pathological affection of the child population was 2542 %, Evenk children 4791 %; the main ranking place among somatic pathology among children, the alien population of the Northern regions, corresponds to those of the children of Slavic group. Besides, the fact that the rate of pathological prevalence among Evenk children in 2 times higher, than among children of the alien population, creates quite a different picture of the distribution of nosological forms. We identified the features of the distribution of polymorphic variants of genes GSTP1 (Ile105Val), TNF-alpha (G308A), IL-10 (G1082A) and IL-4 (C589T) Evenks, which, in our opinion, warrant, together with factors of the external environment, a pattern of morbidity among children of the indigenous residents of Northern Transbaikalia. The data we have on overall morbidity and pathological prevalence of children in studied areas of Transbaikalia correspond with the results of molecular-genetic research.